THE USE OF GOOGLE SCHOLAR IN WRITING RESEARCH PAPER OF QUALITATIVE RESEARCH IN LANGUAGE EDUCATION - Arizal Ikhsan Barokah; Ida Lisdawati (IKIP Siliwangi, 2023)
The development of technology gives positive impacts in education world especially in using search engine to find a legal reference source and avoiding plagiarism. However, students sometimes still find unreliable resources in the internet, which it can be problem for their final project reports and essays. Therefore, one of the new technology is google schoolar as a source of information and reference. Thus, the aim of this research to discuss utilization of google scholar for students in writing research paper. The method used in this study was qualitative which data gained by questionnaires and interview. The participants of this research was consisted of 20 students in qualiatative research in language education class. From the data gained by the researcher, the result showed that 100% students were used google scholar and it indicated that google scholar increased their reference in writing research paper especially in introduction and literature review also it can avoided plagiarism. Furthermore, google scholar makes students are easier to cites than from books and articles in the library or internet. Keywords: Google scholar; Research Paper; Qualitative Research